Characterization and performance of porous photocatalytic ceramic membranes coated with TiO2 via different dip-coating routes - Alias, Siti Salwa; Harun, Zawati; Abd Latif, Intan Suyana (Springer Nature, 2018)
Porous photocatalytic ceramic membranes have been extensively used for separation and purification processes. This study investigates the characterization and performance of porous ceramic membranes coated with TiO2. The flat sheet membranes were prepared via phase inversion. The membranes were dipcoated in different concentrations of TiO2 nanoparticle suspensions (0.01, 0.03 and 0.05 wt%) before sintering or after the sintering process. The ceramic membranes coated with 0.03 wt% TiO2 before sintering at showed excellent morphology with a porous top, dense bottom, and the cross section showed strong adhesion of the penetrated TiO2-coated layer on the surface and within the pores. This membrane exhibited the lowest surface roughness (0.05 lm) and optimum physical properties, permeation of pure water flux (128.28 L m-2 h-1 ), rejection rate (86.06%), better antifouling (highest normalized flux ratio) and self-cleaning performance through increased humic acid rejection flux (94.32 L m-2 h-1 ) and rejection rate (98.56%) subsequent to exposure to UV light. All of the membranes coated with different concentrations of TiO2 prior to the sintering process showed uniform, homogenous coating with enhanced properties and performance. This can be related to the good penetration of TiO2 nanoparticles and better absorption by the membrane structure. The accumulation of closely tied TiO2 nanoparticle suspension on the surface of membranes coated after sintering has essentially blocked the membrane surface and pores which might concurrently explained their reduced performance.